Dietary protein density, cholesterol, egg consumption and mortality in US adults with type 2 diabetes - Wenhao Wang; Jiangyou Li; Zhiyi Zhang; Yinglan Hu; Danli Kong (Medicine, 2026)
Dietary management constitutes a fundamental component of type 2 diabetes (T2D) care. However, the long-term associations of dietary protein, cholesterol, and egg intake with mortality outcomes in the T2D population remain controversial and inconsistent. This study aimed to investigate these associations using a large, nationally representative United States sample. We analyzed data from 3973 adults with T2D participating in the National Health and Nutrition Examination Survey from 1999 to 2018. Dietary intake was assessed via 24-hour dietary recalls. Mortality outcomes, including all-cause, cardiovascular disease (CVD), and diabetes-specific mortality, were ascertained through linkage to the National Death Index through December 31, 2019. Weighted Cox proportional hazards models and restricted cubic splines were employed to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) and evaluate non-linear associations. During the follow-up period, participants in the highest tertile of dietary protein density had a significantly reduced risk of CVD mortality (HR: 0.49; 95% CI: 0.27–0.91; P for trend = .02) compared to the lowest tertile, after adjusting for total energy intake and other confounders. Notably, restricted cubic spline analyses indicated a U -shaped association for all-cause mortality ( P for nonlinearity = .027) and an L-shaped association for CVD mortality, suggesting a threshold effect. Conversely, neither dietary cholesterol nor egg consumption showed significant independent associations with all-cause, CVD, or diabetes-specific mortality in fully adjusted models. Subgroup analysis indicated significant racial disparities ( P for interaction = .028), with the protective association of protein density against all-cause mortality being most pronounced in Mexican Americans (HR: 0.36; 95% CI: 0.15–0.82). In adults in the United States with T2D, an optimal range of dietary protein density is associated with lower CVD mortality risk, particularly among Mexican Americans. Dietary cholesterol and egg consumption are not significantly associated with long-term survival. These findings suggest that nutritional strategies for T2D should prioritize optimizing macronutrient composition with moderate protein consumption, rather than simply increasing intake without limit.